The impact of an integrated care intervention on mortality and unplanned hospital admissions in a disadvantaged community in England: A difference-in-differences study. Issue 6 (June 2022) - Piroddi, Roberta; Downing, Jennifer; Duckworth, Helen; Barr, Benjamin
Highlights: Integrated care often primarily targets utilisation reductions, without considering health inequalities. We evaluated an integrated care intervention where complexities are likely exacerbated by deprivation. The intervention was associated with small increases in unplanned hospitalisation and unchanged survival, with similar effects by deprivation group. Similar integrated care interventions are unlikely to reduce unplanned admissions, increase survival or reduce inequalities in these outcomes. Abstract: Background: Many health systems are experimenting with integrated care models to improve outcomes and reduce healthcare demand. Evidence for effects on health service utilisation is variable, with few studies investigating impacts on mortality or differences by socioeconomic group. Objective: To examine the impact of a multidisciplinary, integrated care team intervention on emergency admissions and mortality, and whether effects differed by deprivation group. Design: A longitudinal matched controlled study using difference-in-differences analysis comparing the change in unplanned emergency admissions twelve months before and after the intervention, and inverse probability of treatment-weighted survival analysis comparing mortality, between intervention and matched control groups. Setting: A relatively deprived city in England, U.K. Intervention: A case-management integrated care programme delivered through multidisciplinary teams and aimed at complex needs and/or high hospitalisation risk patients. Results: The intervention was associated with a small increase in emergency admissions of 15 per 1, 000 patients per month (95% CI 5 to 24, p = 0.003) after the intervention relative to the control group and no significant change in survival between intervention and control groups (HR 0.9, 95% CI 0.84 to 1.13, p = 0.7). Effects were similar across age and deprivation groups. Conclusions: It is unlikely that similar interventions lead to reduced emergency admissions or increased survival. Further studies should use experimental methods and assess impacts on quality of life.